Multiscale microstructural characterization of particulate-reinforced composite with non-destructive X-ray micro- and nanotomography. (15th June 2018) - Nafar Dastgerdi, J.; Miettinen, A.; Parkkonen, J.; Remes, H.
Abstract: Methods based on X-ray tomography are developed to study the relevant statistical quantities describing the microstructural inhomogeneity of particulate reinforced composites. The developed methods are applied in estimating microstructural inhomogeneity parameters of composites containing metallic glass particles in metal matrix, extruded in varying pressure loads. This study indicates that the critical characteristics with regard to the effect of particle clustering are cluster size and shape, local volume fraction of particles in the cluster and the distance between clusters. The results demonstrate that the spatial distribution of reinforcement is very uneven and the amount of particle clustering varies with amount of reinforcement. Moreover, X-ray nanotomography was used to investigate the structure of individual clusters and the results suggest that high extrusion load may cause break-up of individual particle clusters so that their shape changes from solid and spherical to broken and ellipsoidal.